2017
DOI: 10.1111/1750-3841.13861
|View full text |Cite
|
Sign up to set email alerts
|

A Switchable Linker‐Based Immunoassay for Ultrasensitive Visible Detection of Salmonella in Tomatoes

Abstract: The novel switchable linker-based immunoassay is a rapid, specific, and sensitive method that has potential applications for routine diagnostics of Salmonella in tomato products. These advantages make it a practical approach for general use in the processing industry to detect Salmonella rapidly and to implement appropriate regulatory procedures. Furthermore, it could be applied to other fresh products including cantaloupe, strawberry, and cucumbers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…Typhimurium, which conrmed the selectivity of SL-based assay in the previous study, was used as a representative strain. 35 As shown in Fig. 6, the REVC shi occurred at a linker concentration of 15 mg mL À1 , as compared to the control in the tested Salmonella Typhimurium samples (10 2 , 10 4 , and 10 6 CFU/ 400 mL).…”
Section: Evaluation Experimentsmentioning
confidence: 80%
See 2 more Smart Citations
“…Typhimurium, which conrmed the selectivity of SL-based assay in the previous study, was used as a representative strain. 35 As shown in Fig. 6, the REVC shi occurred at a linker concentration of 15 mg mL À1 , as compared to the control in the tested Salmonella Typhimurium samples (10 2 , 10 4 , and 10 6 CFU/ 400 mL).…”
Section: Evaluation Experimentsmentioning
confidence: 80%
“…In addition, in previous studies, we reported that the SL-based assay could work in serum as well as in various food matrices such as tomato and milk. [34][35][36][37] Therefore, we dealed with the minimum environmental factors (salt and pH) in this study.…”
Section: System Stability Of Ph and Salt Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging detection methods are independent of gene amplification, and the common strategy is based on the surface modification of AuNPs with Abs, proteins, and aptamers. The peak absorbance exhibits a red shift with an increase in size and/or aggregation of AuNPs, giving stable AuNPs' solution red color, while the aggregated state of AuNPs produces purple color (Hahn et al, 2017;Sanromán-Iglesias et al, 2015;You et al, 2020).…”
Section: Pathogensmentioning
confidence: 99%
“…Further, this method was used for the detection of Salmonella spp. in tomatoes (Hahn et al, 2017) with agitation, which was a step suggested for more rapid detection. The detection limit of Salmonella in tomato was 10 CFU/g.…”
Section: Aunp Aggregationmentioning
confidence: 99%